(untitled) (Public Sector Economics - submission site, 2023)
Based on the Euro Social Survey, we show that Croatians’ values do not predict perfectly their political partisanship. This feature may be a consequence of the lack of interest of Croatian people on politics, which explains the significantly lower electoral turnout in Croatia. Besides, surprisingly, Croatians’ judgment of government’s performance is more unfavourable when their party holds power. Political polarization is increasing, which jeopardizes the median voter assumption. Besides, trust of Croatians in parliament and politicians is extremely low. Most probably, it is due to high corruption and to the post-communism effect (the belief that the state worked against the individual rather than for it). Croatia missed the opportunity to implement ambitious reforms when opting to join the EU and NATO. However, the Croatian budgetary process performs very well, which is a very positive feature that should increase the engagement of Croatians in their government, economy and political system.